Human Resource Management in Improving Teacher Professionalism at an Nizam Private Junior High School - Rubino; Muhammad Rifa'i; Muhammad Fadhli (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
The existing research tends to discuss only towards improving teacher professionalism, while this research will discuss, explain and examine human resource management (HRM) in improving teacher professionalism at An Nizam Junior High School can be implemented in various ways. One way is to use the school management system (SIM Sekolah) to manage teaching schedules. This research fulfills the characteristics of qualitative research. This research is a field research using a phenomenological approach. Data collection techniques were carried out by: 1) Observation; 2) Interviews and 3) Documentation Studies. Analysis consists of three streams of activities that occur simultaneously, namely: data reduction, data presentation, conclusion drawing/verification. The data validity test in qualitative research includes, data credibility test, transferability test, dependability test, and confirmablity test. the results of the research findings found several core components carried out by An Nizam Private Junior High School in the teacher recruitment process, among others: 1) Digitalization of brochures, 2) Academic/Non-Academic Requirements, 3) Having the same vision and mission as An Nizam Private Junior High School, 4) Evaluation. In the teacher selection process, among others: 1) The existence of a selection instrument, 2) Implementation of selection and ability, 3) Micro teaching, 4) Job description. As for what An Nizam Private Junior High School does in developing teacher education and training: 1) External education and training, 2) Internal education and training, 3) Education and training related to teacher competencies. In the development of teacher education and training, among others, 1) Salary, 2) Umrah rewards for qualified teachers, 3) Intensive for teachers who have memorized at least 1 Juz of Qur'an